ЗҮҮН ХОЙД АЗИ БА МОНГОЛЫН ГАДААД БОДЛОГЫН ЗАРИМ АСУУДАЛ - С.Мөнхбат (Politology, 2023)
The Northeast Asia is third significance region for Mongolian geostrategic and foreign policy. The Northeast Asian region has been getting more global attention, due to the rapid development of economies such as China and South Korea resulting in enhanced coordination and cooperation among countries, mainly in economic affairs. On the other hand, this region is considerably rich in political, economic, ethnic and religious diversity and conflict between countries (North and South Korea). Pecause of these reasons major changes in the security environment have yet to emerge and long- standing issues of territorial rights and reunification continue to plague the region. This article purpose is to study the external political and economic conditions of Mongolia in the Northeast Asian region.